The Other Talent War : Competing through Alumni - Carnahan, Seth; Somaya, Deepak (MIT Sloan Management Review, 2015)
Companies increasingly recognize the value of maintaining good relationships with former employees. Recent research, however, reveals a new insight: It's also wise to pay attention to what your competitors' former employees are up to.